2007
DOI: 10.1007/s10067-006-0495-8
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expression of mast cell tryptase and protease activated receptor-2 in synovia of rheumatoid arthritis and osteoarthritis

Abstract: The objective of this study is to examine the differential expression of mast cell tryptase and its receptor, protease-activated receptor-2 (PAR-2), in the synovium and synovial fluid of patients with rheumatoid arthritis (RA) and osteoarthritis (OA). Biochemical and immunohistochemical analyses were performed to determine whether the trypsin-like protease in the synovium is identical to mast cell tryptase. The effects of mast cell tryptase on the proliferation of synovial fibroblast-like cells (SFCs) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 42 publications
5
46
0
Order By: Relevance
“…Tryptase and chymase can further promote ECM degradation by activating proMMPs (80)(81)(82)(83)(84) and pro-uPA (85). Mast cell tryptase is important in activating PAR-2 on synovial fibroblasts and inducing proinflammatory cytokine release (86,87). Tryptase can also enhance the release of vascular endothelial growth factor from chondrocytes, although this appears to be a PAR-independent event (88).…”
Section: Immune Cell-derived Serine Proteinasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tryptase and chymase can further promote ECM degradation by activating proMMPs (80)(81)(82)(83)(84) and pro-uPA (85). Mast cell tryptase is important in activating PAR-2 on synovial fibroblasts and inducing proinflammatory cytokine release (86,87). Tryptase can also enhance the release of vascular endothelial growth factor from chondrocytes, although this appears to be a PAR-independent event (88).…”
Section: Immune Cell-derived Serine Proteinasesmentioning
confidence: 99%
“…Synovial fibroblasts, chondrocytes, macrophages, neutrophils, mast cells, T cells, and dendritic cells all express PARs, which exhibit both antiinflammatory and proinflammatory properties, although recent data point toward a detrimental role especially in the context of immune-mediated effects in arthritis (157). A study in PAR-2 Ϫ/Ϫ mice confirmed PAR-2 as a key mediator of chronic joint inflammation (158), and this is likely to be a consequence of activation by mast cell-derived tryptase (86,87). PAR-2 is associated with the perpetuation of inflammation in both RA and OA, because PAR-2 levels are elevated by proinflammatory cytokines and growth factors (159,160), while PAR-2 activation in peripheral blood monocytes and chondrocytes enhances proinflammatory cytokine production (161,162).…”
Section: Serine Proteinases and Cell Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated mast cell counts in the synovial fluid of patients with OA have been reported, with higher levels of histamine, tryptase, and nitrite detected in OA synovial fluid. 60,61 Furthermore, a role for TNF-a in the induction of mast cell chemotaxis in OA has been elucidated. 62 Studies have suggested that the observed increase of mast cells in OA may be due to the expansion of a tryptase but not chymase containing population, with an increase in this population reported in the synovial tissue of OA patients compared with control.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Various theories on the pathology of osteoarthritis are being investigated that may lead to new therapeutic options. These relate to the role of skeletal muscle (11)(12)(13)(14), the effect of nucleic acid metabolism (15,16), sex gland functions (17)(18)(19), the action of stable mast cells (20,21) and the importance of the subchondral vascular system (9,22,23) in osteoarthritis and its progression. In the present review, the possibility that vitamin E may be able to delay the progression of osteoarthritis was explored through studying the potential role of this nutritional factor in each of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%